Penerimaan Masyarakat Terhadap Penertiban Pedagang Liar Pada Area Parkir Pasar Larangan Sidoarjo - Sekar Fatima Permata Buana; Nabila Frika Izza Sabrina; Rofi Ziyat Rizky; Suhartin Ruslin; Amirul Fahmi Yusuf (Universitas Palangka Raya, 2024)
This research aims to determine the community's response to the implementation of controlling illegal traders in the parking area of ​​Pasar Larangan Sidoarjo. The research results show that the public has various views on controlling illegal traders. Most people disagree because it is not effective in overcoming parking problems in market areas, because not only illegal traders but also illegal parking disturbs the surrounding community. Based on 2020 Kompas data, illegal parking violations involved 56,902 vehicles and were dominated by motorbikes. From data from the East Java Province Central Statistics Agency, the number of motorized vehicles from 2018 - 2020 continues to increase. There were around 1,636,032 in 2018, then 1,750,445 in 2019, and increased to 1,808,754 in 2020. The number of vehicles is certainly not comparable to the parking space provided by the Sidoarjo Prohibition market. Apart from that, a small portion of the community still supports enforcement to reduce chaos, increase comfort and order in the market area. It is hoped that this research can contribute to the development of a more effective strategy in overcoming the problem of illegal traders in the Sidoarjo prohibited market parking area.